Assessment of Nutrient Expert Tool for Fertilizer Management in Rice at Fulbari, Chitwan, Nepal - Acharya, Milan; Khanal, Prabha; Marahatta, Santosh; Sah, Shrawan Kumar; Subedi, Purushottam (Agronomy Journal of Nepal, 2022)
A field trial was conducted at Fulbari, Chitwan in 2017 to evaluate the growth, productivity and economics of rice production under different nutrient management practices. Trial was laid out in a split-plot design with five replications. The main plot factor consisted of two rice varieties (Radha-4; improved variety and Arize Tej Gold; a popular Hybrid) and subplot factor consisted of five different nutrient management practices farmers’ applied dose (FAD;0-20:0-15:0-18 NPK kg ha-1), government recommended dose (GRD; 100:30:30 NPK kg ha-1), NARC recommended dose (NRD; 120:60:40 NPK kg ha-1), LCC based N and NE® based P, K dose (LCC-N+NE-P,K; 90-115:5-22:17-50 NPK kg ha-1 for Radha-4 and 90-140:5-36:38-73 NPK kg ha-1 for Arize Tej Gold), Nutrient Expert® based NPK dose (NED; 93-109:5-22:17-50 NPK kg ha-1 for Radha-4 and 118-125:5-36:38-73 NPK kg ha-1 for Arize Tej Gold). Data regarding biometrical, phenological, and yield attributes were recorded at regular intervals. Results revealed that different nutrient management practices had a significant influence on growth, yield attributes, and yield of rice.  Number of effective tillers per square meter (215.62), number of grains per panicle (132.52), panicle length (27.02 cm) was recorded higher in LCC-N+NE-P, K. Similarly, a number of grains per panicle and panicle length in LCC-N+NE-P, K were statistically similar to NED. Significantly higher grain yield (5.19 Mt ha-1) and straw yield (6.43 Mt ha-1) were recorded in LCC-N+NE-P, K compared to FAD but statistically similar to NED. Higher Benefit-cost (B:C) ratio (2.41) was obtained in LCC-N + NE – P, K which was statistically similar to FAD and NED. Thus, the combined use of LCC and Nutrient Expert software for nutrient management in rice was found productive and profitable in western Chitwan.